2006
DOI: 10.3233/jad-2006-10109
|View full text |Cite
|
Sign up to set email alerts
|

The use of laboratory tests in patients with Mild Cognitive Impairment

Abstract: Cognitive decline in elderly people can be caused by a specific and treatable metabolic disorder, and the use of laboratory tests is recommended as part of the diagnostic workup of patients with dementia. Patients with mild cognitive impairment (MCI) are commonly investigated by a similar laboratory diagnostic workup, however it is not known whether this clinical practice is justified. In the present study, we compared the frequencies of laboratory abnormalities, and laboratory abnormalities relevant for cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…It is interesting to note that, in spite of vitamin B12 being tested as part of the standard laboratory diagnostic workup for patients with cognitive complaints at the Memory Clinic in Lisbon, only 3.2% of all MCI patients observed in this institution during the period of 2002 to 2012 had decreased serum values of vitamin B12, confirming a low frequency of vitamin B12 deficiency in MCI patients [6]. Nowadays, in clinical practice, the prevalence of reversible dementias is declining [42] and the identified metabolic abnormalities are often not the main cause responsible for the cognitive symptoms when compared with the neurodegenerative pathology [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that, in spite of vitamin B12 being tested as part of the standard laboratory diagnostic workup for patients with cognitive complaints at the Memory Clinic in Lisbon, only 3.2% of all MCI patients observed in this institution during the period of 2002 to 2012 had decreased serum values of vitamin B12, confirming a low frequency of vitamin B12 deficiency in MCI patients [6]. Nowadays, in clinical practice, the prevalence of reversible dementias is declining [42] and the identified metabolic abnormalities are often not the main cause responsible for the cognitive symptoms when compared with the neurodegenerative pathology [43].…”
Section: Discussionmentioning
confidence: 99%
“…In a consecutive series of patients observed in a memory clinic, 3.3% of patients with Mild Cognitive Impairment (MCI) had low serum values of vitamin B12 [6]. MCI is usually considered a transitional state between normal cognitive aging and dementia [7].…”
Section: Introductionmentioning
confidence: 99%
“…of subjects > 65 years: 3103 (63.3%) 44.8% F Hyponatremia related to heart failure, liver cirrhosis, diabetes, malignancy, diuretic use Dementia diagnosed according to ICD-9-CM Furosemide, thiazides. Dosage not reported Hyponatremia as a predictor of dementia C. Fujisawa et al (2021) [ 49 ] Prospective cohort Not reported Serum sodium < 135 mEq/l Single at baseline 2982 82.0 (76.0–84.0) in hyponatremic vs 79.0 (75–83) in normonatremic Median years (IQR) 48% F Hyponatremia related to cardiac disease, liver disease, diabetes, diuretic use MMSE, FAB, Digit span forward, Digit span backward, category fluency, logical memory Type and dosage of diuretics not specified Association between hyponatremia and cognitive impairment, muscle mass, physical performance Gosch et al (2012) [ 13 ] Case control 128 ± 3.2 mEq/l (mean ± SD) in hyponatremic group Serum sodium < 135 mEq/l Single at admission 2880 78.6 (6.98) Mean years (SD) 75.6% F Hypo- (4.7%), and normo-osmolar (1.6%) hyponatremia, adverse drug reaction (15.5%), hyponatremia related to heart failure (3.1%), severe liver disease (0.8%), cancer (1.6%), adrenal insufficiency (1.6%), SIADH (0.8%) MMSE, clock completion Type and dosage of diuretic not specified Effect of hyponatremia on CGA Pereira et al (2006) [ 50 ] Prospective cohort Not reported Serum sodium < 135 mEq/l Single at baseline 306 74 (8.7) Mean years (SD) 50.33% F Not evaluated BLAD Not evaluated Frequency of laboratory abnormality in MCI and dementia Suárez et al (2020) [ …”
Section: Methodsmentioning
confidence: 99%
“…published between 2006 and 2021 were included (12,33,(57)(58)(59). Three studies were prospective (57-59) and two retrospective (12,33) (Table 3).…”
Section: Hyponatremia and Cognitive Impairmentmentioning
confidence: 99%